2009
DOI: 10.1007/s10327-009-0168-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and variability analysis of Apple scar skin viroid in India

Abstract: Apple scar skin viroid (ASSVd) infection is a major limitation to apple fruit quality and causes huge economic losses. In surveys of apple orchards in the northern Indian state of Himachal Pradesh, fruits with dappling symptoms were noticed. ASSVd was detected from these fruits and molecularly characterized. Ten clones from three isolates were sequenced, of which seven were new sequence variants of ASSVd. The clones had significant sequence variability (94-100%) with each other. Variability was more common in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…However, not only was this study able to transfer ASSVd to various herbaceous hosts, but it was also readily transmissible via several inoculation methods. Indian isolates of ASSVd are variable in their pathogenicity domain in comparison to other isolates (Walia et al ., ) and variations in the P‐domain in other viroids are known to affect replication efficiency, symptom expression and host range (Owens et al ., ). This might be the reason for efficient transfer of ASSVd (Indian isolate) to herbaceous hosts, in contrast to the previous reports about its non‐transmission.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, not only was this study able to transfer ASSVd to various herbaceous hosts, but it was also readily transmissible via several inoculation methods. Indian isolates of ASSVd are variable in their pathogenicity domain in comparison to other isolates (Walia et al ., ) and variations in the P‐domain in other viroids are known to affect replication efficiency, symptom expression and host range (Owens et al ., ). This might be the reason for efficient transfer of ASSVd (Indian isolate) to herbaceous hosts, in contrast to the previous reports about its non‐transmission.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported in the case of Citrus bent leaf viroid (CLBVd), which also belongs to the genus Apscaviroid, that progeny variants have changes located mostly in the terminal left domain of the secondary structure, which is considered to be a variable domain (Foissac & Dur an-Vila, 2000;Gand ıa & Dur an-Vila, 2004). Most of the changes in the Indian isolates of ASSVd also appeared in the left portion of the viroid secondary structure (Walia et al, 2009). Earlier reports for viroids in the family Pospiviroidae suggested that variability of viroids is found mainly in the V and P domains (Keese & Symons, 1985).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…E-mail address: lisa.ward@mpi.govt.nz (L. Ward). severity of symptoms usually increases with fruit ripening (Walia et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…2007), a survey was undertaken to examine the viroids infecting the Himalayan wild cherry. In context of our research on viroid infecting Indian apple, ASSVd was initially reported on apple from India causing severe symptoms of dappling and scarring on apple fruits (Walia et al. 2008) thus we were keen to know that does viroids particularly ASSVd also infects the Himalayan wild cherry and produces symptoms typical of ASSVd infection.…”
mentioning
confidence: 99%